Fenomena Orang Biasa Menjadi Konten Kreator Di Facebook Pro (Studi Naratif Tentang Perubahan Gaya Komunikasi) - Putri Sahri Aprilia; Sandra I.Telussa; Olivia Tahalele (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to analyze the phenomenon of ordinary people becoming content creators on Facebook Pro and to understand the changes in communication style that occur in the process in Ambon City. The study is motivated by the development of Facebook Pro, which provides opportunities for the general public to become content creators through its monetization features, thereby encouraging changes in the role of social media users from merely consumers to content producers while at the same time forming new digital identities. This study used a qualitative method with a narrative study approach. The research informants consisted of six Facebook Pro content creators in Ambon City. Data were collected through in-depth interviews, observation, and documentation. The results of the study show that the informants experienced changes in their communication style, characterized by increased self-confidence, the use of more communicative and persuasive language, the ability to construct stories (storytelling), and increased interaction with audiences through comments, likes, and followers. Based on the narrative analysis, the informants’ experiences fulfill the elements of coherence, narrative fidelity, narrative structure, and moral messages that reflect the process of transformation from ordinary users into content creators. The study also shows that Facebook Pro has shifted the position of the public from merely media consumers to producers of digital narratives who actively construct identities and relationships with audiences.